Restrictions or possibilities? – Visitor management in the Börzsöny landscape unit of Danube-Ipoly National Park (Hungary) - Benkhard, Borbála; Előd, Réka; Erdős, Katalin Martonné (Turizam, 2018)
The objectives of this paper is to survey the touristic infrastructure, services and regulations in the Börzsöny Mountains not far from Budapest and to define those measures that can be considered as visitor management tools. As a result the implementation of such visitor management methods may become more effective and strategic. All factors involved in the survey had been collected on field examinations and through personal interviews with the specialists of the two most important touristic organisation of the area (national park and Ipoly Forest cInc). Potential advantages had been defined accordingly to references and on our previous surveys. After the aggregation of measures and tools that can be considered as visitor management methods, it has been determined that besides creating more awareness of the benefits of those, we need to put more emphasis on informing visitors and the application of tools supporting the adherence of restrictions. Accordingly, we expect that further to protecting attractions there will be less conflicts.